CRIMINAL LAW EDUCATION AS A COMPONENT OF THE NATIONAL SECURITY SYSTEM OF THE REPUBLIC OF BULGARIA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Criminal law is deeply connected with human nature, because it indicates the natural striving of the individual after safety and prosperity. Criminal law is a civilized form of measuring and limiting the fear of violence and arbitrariness in the human community. Insofar as criminal law practice is a mechanism for creating an assessment and a fair resolution of a dangerous life conflict, it is also a mechanism for creating safety, reassurance and satisfaction of the socially organized person. Criminal law education is an important component of the national security system of the Republic of Bulgaria. With its help it is possible to successfully train and educate human resources supposed to recognize, realize and manage the emerging risks, especially (but not only) in the justice, judicial and educational systems of the state.  The products (legal acts/deeds) of a knowledgeable person in the field of criminal justice are of universal value and usefulness. It could and should be successfully invested in the sphere of national security as public welfare through criminal law education. Quality criminal law education accelerates, enriches and expands the field of application of the fight against crimes as one of the important modern tests in the rule of law. In this sense, it contributes in its own way to the understanding of the dilemma, levels, classification and management of national security in the rule of law. By the way, the rule of law is both a goal and a means of national security. Improving the quality of criminal law education in the conditions of a changing social environment leads to a budget and safe increase in the quality and quantity of the national security in the Republic of Bulgaria. Educating knowldeable and decent citizens increases national security by reducing mistrust between individual members of society. With some reservations - an educated person is more reasonable, more responsible, more creative and more predictable than an uneducated one.